Meropenem Use for Bacterial Infection at a Hospital in Bandung City - Winni Maharani; Usep Abdullah Husin; Syahrir Zein Rumatumia; Tresna Ridha Nurramadhani; Lia Marlia Kurniawati; Djatnika Setiabudi (Global Medical & Health Communication (GMHC), 2026)
Meropenem is a beta-lactam antimicrobial agent used to treat broad-spectrum bacterial infections and is classified as a reserve antibiotic. The Antimicrobial Resistance Control Program (PPRA) at the hospital monitors the use of meropenem to ensure it is used appropriately and in accordance with antimicrobial stewardship principles. This study aims to determine the preliminary pattern of meropenem antibiotic use at the hospital, Bandung, during 2019–2020. It is an observational descriptive study using secondary medical record data with a total sampling method. A total of 182 study subjects were all patients treated with meropenem from various departments, and the diagnoses met the criteria for culture results. Data analysis included the distribution proportion of the observed variables. This study shows that the pattern of meropenem use over two years is characteristic of patient age with the most similar patterns in the age categories under 0–10 years, 51–60 years, and 61–70 years (21–26%), however, there were differences in gender in 2019, female patients were more numerous than male patients, while in 2020 were the opposite. Other results show similar diagnostic patterns in both years, with the most common diagnoses being respiratory tract infections, which continued to increase in the following years (27% and 35%). Conversely, the majority of culture results in the two years were negative (58% and 72%). The possibilities here relate to specimen preparation or to prior antimicrobial use before hospital admission. In conclusion, the pattern of meropenem antibiotic use at the hospital is similar in characteristics, diagnostics, and culture results. The PPRA Committee is expected to improve the policy on meropenem use in accordance with government regulations and prevent antimicrobial resistance.